Semicontinuous Bioreactor Production of Recombinant Butyrylcholinesterase in Transgenic Rice Cell Suspension Cultures - Corbin, Jasmine M.; Hashimoto, Bryce I.; Karuppanan, Kalimuthu; Kyser, Zachary R.; Wu, Liying; Roberts, Brian A.; Noe, Amy R.; Rodriguez, Raymond L.; McDonald, Karen A.; Nandi, Somen (Frontiers in Plant Science, 2016)
An active and tetrameric form of recombinant butyrylcholinesterase (BChE), a large and complex human enzyme, was produced via semicontinuous operation in a transgenic rice cell suspension culture. After transformation of rice callus and screening of transformants, the cultures were scaled up from culture flask to a lab scale bioreactor. The bioreactor was operated through two phases each of growth and expression. The cells were able to produce BChE during both expression phases, with a maximum yield of 1.6 mg BChE/L of culture during the second expression phase. Cells successfully regrew during a 5-day growth phase. A combination of activity assays and Western blot analysis indicated production of an active and fully assembled tetramer of BChE.